2013
DOI: 10.18869/acadpub.aums.2.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Determine the Effects of Zinc Supplementation on Insulin Resistance, Lipid Profiles and Blood Glucose in Obese People

Abstract: ‫ﻧﺸﺮﻳﻪ‬ ‫دوره‬ ‫اﻟﺒﺮز،‬ ‫ﭘﺰﺷﻜﻲ‬ ‫ﻋﻠﻮم‬ ‫داﻧﺸﮕﺎه‬ ‫آﻣﺎري‬ ‫آﻧﺎﻟﻴﺰ‬ ‫آﻣﺎري‬ ‫اﻓﺰار‬ ‫ﻧﺮم‬ ‫از‬

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In a study by Khan et al 12 , demonstrated that 50 mg elemental zinc as zinc sulphate supplementation for 12 weeks in type-2 diabetes with microalbuminuria patients has resulted in a significant decrease in triglycerides, VLDL-cholesterol and a significant rise in HDL-cholesterol levels, whereas there was no significant decrease in total cholesterol and LDL-cholesterol concentrations. In addition, in another study by Payahoo et al 27 was observed that received 30 mg zinc gluconate per day among healthy obese adults did not significantly change lipid profile biomarkers but triglycerides levels were significantly decreased. However, the administration of 440 mg/day zinc supplements for 5 weeks has also reported no significant changes in triglycerides, total cholesterol and LDL-cholesterol levels at the end of the study 28 .…”
Section: Discussionmentioning
confidence: 88%
“…In a study by Khan et al 12 , demonstrated that 50 mg elemental zinc as zinc sulphate supplementation for 12 weeks in type-2 diabetes with microalbuminuria patients has resulted in a significant decrease in triglycerides, VLDL-cholesterol and a significant rise in HDL-cholesterol levels, whereas there was no significant decrease in total cholesterol and LDL-cholesterol concentrations. In addition, in another study by Payahoo et al 27 was observed that received 30 mg zinc gluconate per day among healthy obese adults did not significantly change lipid profile biomarkers but triglycerides levels were significantly decreased. However, the administration of 440 mg/day zinc supplements for 5 weeks has also reported no significant changes in triglycerides, total cholesterol and LDL-cholesterol levels at the end of the study 28 .…”
Section: Discussionmentioning
confidence: 88%
“…Plasma Zn concentrations respond to Zn supplementation (31,40) . To date, published studies of supplementation trials of Zn for diabetes prevention and management are mostly of small sample sizes and short duration.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes from the few published clinical trials in Table 1 [28][29][30][31][32][33][34][35] evaluating the effect of dill ingestion on dyslipidemia and measures of glycemic control were inconclusive. The influences of dill intake on blood glucose levels, lipid profiles, and determinants of insulin resistance were inconsistent.…”
Section: Cardiovascular Disease and Type 2 Diabetes Mellitus (T2dm) R...mentioning
confidence: 99%